Novel irreversible electroporation ablation (Nano-knife) versus radiofrequency ablation for the treatment of solid liver tumors: a comparative, randomized, multicenter clinical study - Zhang, Xiaobo; Zhang, Xiao; Ding, Xiaoyi; Wang, Zhongmin; Fan, Yong; Chen, Guang; Hu, Xiaokun; Zheng, Jiasheng; Xue, Zhixiao; He, Xiaofeng; Zhang, Xin; Wei, Yingtian; et al. (Frontiers in Oncology, 2022)
Background: Irreversible electroporation (IRE) is a soft tissue ablation technique that uses short electrical fields which induce the death of target cells. Purpose: To evaluate the safety and efficacy of an IRE-based device compared to regular radiofrequency ablation (RFA) of solid liver tumors. Material and methods: In this multicenter, randomized, parallel-arm, non-inferiority study, 152 patients with malignant liver tumors were randomized into IRE (n = 78) and RFA (n = 74) groups. The primary endpoint was the success rate of tumor ablation; the secondary endpoints included the tumor ablation time, complications, tumor recurrence rates and treatment-related adverse events (TRAE) Results: The success rate of tumor ablation using IRE was 94.9% and was non-inferior to the RFA group (96.0%) (P = 0.761). For the secondary endpoints, the average ablation time was 34.29 ± 30.38 min for the IRE group, which was significantly longer than for the RFA group (19.91 ± 16.08 min) (P < 0.001). The incidences of postoperative complications after 1 week (P = 1.000), 1 month (P = 0.610) and 3 months (P = 0.490) were not significantly different between the 2 groups. The recurrence rates of liver tumor at 1, 3 and 6 months after ablation were 0 (0.0%), 10 (13.9%) and 10 (13.3%) in the IRE group and 2.9%, 7.3% and 19.7% in the RFA control group (all P > 0.05), respectively. For safety assessments, 51 patients experienced 191 AEs (65.4%) in the IRE group, which was not different from the RFA group (73.0%, 54/184) (P = 0.646). In 7 IRE patients, 8 TRAEs (7.9%) occurred, the most common being edema of the limbs (mild grade) and fever (severe grade), while no TRAEs occurred in the RFA group. Conclusion: This study proved that the excellent safety and efficacy of IRE was non-inferior to the regular radiofrequency device in ablation performance for the treatment of solid liver tumors. Clinical trial registration: Chinese Clinical Trial Registry: ChiCTR1800017516